Follow me, boys! [videorecording (DVD)] - Tokar, Norman, 1920-1979; MacMurray, Fred, 1908-1991; Miles, Vera; Gish, Lillian, 1893-1993; Ruggles, Charlie, 1886-1970; Reid, Elliott, 1920-2013; Russell, Kurt; Patten, Luana, 1938-1996; Murray, Ken, 1903-1988; Kantor, MacKinlay, 1904-1977 (Disney DVD., 2004)
Lem Siddons decides to put down roots after one too many years on the road with a ramshackle jazz band. He marries his sweetheart Vida Downey, and becomes a scoutmaster.